THE SPECIES OF PRIONYX VAN DER LINDEN, 1827 (HYMENOPTERA: SPHECIDAE) IN THE MAGELLAN REGION, CHILE (Acta Entomológica Chilena, 2022)
Twospeciesof Pnonyx Van der Linden, 1827. P neoxenus (Kohl, 1890) and P nolonitidum (Willink, 1951),are cited for the First time at Magellan Región. Same taxonomic characlers and geographic dislributionare analized.